Some main conclusions drawn from a basinal analysis of the Dwyka series in the Karroo basin - Stratten, T. (Bernard Price Institute for Palaeontological Research, 1968)
The investigation of the Dwyka glaciation and its relationship to the pre-Karroo surface was undertaken as a research project at the University of the Witwatersrand under the sponsorship of Union Corporation, Limited. A thesis on this study has been submitted for the degree of Doctor of Philosophy under the supervision of Professor T. W. Gevers. The research fell mainly into two separate but related fields of study. The first field was to investigate the pre-Karroo surface with special reference to the geology beneath the Karroo System. The second field was to investigate the paleo-ice flow directions of the Dwyka Tillite and relate this to the position and lithology of the source areas.
Main article
Keywords: Dwyka; Karroo basin; geology; paleo-ice flow